Financial viability of Peste des Petits Ruminants (PPR) control programme (PPR-CP) implemented in Madhya Pradesh, India - NAIDU, GOVINDARAJ GURRAPPA; VINAYAGAMURTHY, BALAMURUGAN; TAPASE, JAYANT; VERMA, NAGEEN; MOHANTY, BARADA SHANKAR; KUMAR, NAVEEN; SHOME, BIBEK RANJAN; ROY, PARIMAL (The Indian Journal of Animal Sciences, 2023)
Madhya Pradesh (MP) state in India had practiced focussed vaccination against Peste des Petits Ruminants (PPR) from 2006-07 to 2015-16 and adopted PPR-Control Programme (PPR-CP) with 100% coverage during first year followed by 30% bi-annual vaccination for two years since 2016-17. This study evaluated the impact of PPR-CP using secondary data and cross-sectional survey data collected from 410 and 340 flocks before (during 2015-16, survey-I) and after PPR-CP implementation (during 2018-19, survey-II), respectively. Besides the incidence and disease cost, Incremental Benefit Cost Ratio (IBCR) was calculated to assess the financial viability of PPR- CP implementation in MP state under actual vaccination coverage after PPR-CP (scenario-I) and as per defined PPR-CP strategy (scenario-II). The number of PPR affected flocks declined significantly from 14.9% to 4.6% and the disease incidence declined from 27.5% to 10.2% in sheep and 18.8% to 0.64% in goats, in survey-I and II, respectively. The projected loss before and after PPR-CP was ` 3260 million (` 326 crore) and ` 476 million (` 47.6 crore), respectively. Financial viability of PPR-CP revealed an IBCR of 69.8:1 and 39.4:1 under scenario-I and II, respectively. Estimated incremental benefits outweighed the incremental cost in both vaccination scenarios, however, as per current vaccination plan (scenario-I), no fresh cases were reported for two years following PPR-CP, but reoccurred during 2019-20, as the state did not comply with PPR-CP Strategy. Therefore, selecting the right vaccination strategy and its diligent implementation may aid in eradicating PPR by 2030 in India in line with PPR global strategy.